International prestige through sporting success? Searching empirical evidence - Haut, J. (Diskussionspapiere des Europäischen Instituts für Sozioökonomie e. V., 17, 2016)
A central argument for public funding of elite sport is the claim that success at Olympic Games or world championships would lead to increasing international prestige for the country as a whole. While this assumption seems plausible in general, it clearly lacks specification. Therefore, in a first step several theoretical approaches are discussed, in order to unpack which forms of prestige can be sought by states in which kind of sports and events. Subsequently, the (rather limited!) state of empirical research on the topic is summarized. The few available results already reveal that the formula "the more success, the more prestige" is all too simple. As a consequence, possible methodological approaches and available indicators for sport-induced changes in international prestige are presented and discussed. The paper concludes by suggesting concrete steps towards a more systematic analysis of the questions at stake.